2015
DOI: 10.1007/s00520-015-2635-7
|View full text |Cite
|
Sign up to set email alerts
|

Management of the extravasation of anti-neoplastic agents

Abstract: Several strategies must be established to ensure that extravasation is recognized and properly managed. Given the evidence available at this time, the Comité de l'évolution des pratiques en oncologie (CEPO) has made recommendations for clinical practice in Quebec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1
31

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 42 publications
0
46
1
31
Order By: Relevance
“…A standardised interdisciplinary approach to manage extravasations of cytotoxic agents should be implemented in the hospital quality management system [4, 17]. A task force quickly accumulates the necessary expertise to handle even complex situations and raises the awareness for this complication in the entire institution.…”
Section: Discussionmentioning
confidence: 99%
“…A standardised interdisciplinary approach to manage extravasations of cytotoxic agents should be implemented in the hospital quality management system [4, 17]. A task force quickly accumulates the necessary expertise to handle even complex situations and raises the awareness for this complication in the entire institution.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,18,19,[165][166][167] All were limited in their applications to different patient groups and few reported on the potential harms or side effects that may occur from a particular course of treatment. In addition, the criteria on which studies were included and an assessment of the quality of these studies were not reported in any of the published guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,18,19,[165][166][167] Two of the references 165,166 reported on the same set of guidelines but both were available only as conference abstracts, limiting the information that could be extracted from them. Of the remaining five references, one was a general document which included guidelines for all types of extravasation injuries, 2 one focused on a paediatric population, 19 and the remaining three limited their scope according to the type of fluid extravasated.…”
Section: Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations